Peran Dinas Sosial terhadap Penyandang Masalah Kesejahteraan Sosial (PMKS) di Kabupaten Lima Puluh Kota - Azizurrahman H, Muhammad; Jumiati, Jumiati (Policy, Law and Political Research Center, 2023)
This research was conducted using a qualitative approach with descriptive methods, in determining researcher informants using purposive sampling methods and techniques. Data collection techniques are carried out by interviews, observation, and documentation. In testing the validity of the data, researchers used method triangulation techniques. As for data analysis techniques using data reduction, data presentation, and conclusions. The results of this study conclude as follows; (1) The role of the Social Service towards people with social welfare problems (PMKS) in Fifty City District, namely (1) the role of facilitators by providing education and training to people with social welfare problems in order to improve their skills in overcoming problems and building independence. (2) the role of education carried out by raising awareness such as children facing the law (ABH). (3) representational roles by building partnerships. The representational role of the Fifty City District Social Office involves building partnerships with various parties, including NGOs, community organizations, and other related parties. (4) the technical role of the Fifty City District Social Office towards people with social welfare problems by providing social service delivery includes the provision of financial assistance, access to mental health services, housing services, counseling, and employment guidance. Meanwhile, the inhibiting factors for the role of Social Services towards people with social welfare problems (PMKS) in Fifty City Regency are limited resources and lack of public awareness.